Passos cambaleantes, caminhos tortuosos: Beber cachaça, prática social e masculinidade - Recife/PE - 1920 -1930 - Rosa, Ana Lúcia Gonçalves (2003)
It is common nowadays to see cachaça and masculinity as synonymous, that is, the practice of drinking alcohol being seen naturally as a masculine attribute [...]